PENGARUH JOB CRAFTING TERHADAP KETERIKATAN KERJA DAN KEPUASAN KERJA PADA KARYAWAN PT. PERTA ARUN GAS (PAG) LHOKSEUMAWE - Yuli Monita; Mahdani Mahdani (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2020)
This study aims to measure the effect of job crafting on work engagement and job satisfaction. The population used in this study are companies that work in the company PT. Perta Arun Gas (PAG) consisted of 180 employees. The sample used amounted to 123 people. The sampling technique uses probability sampling and the type of sampling is Simple Random Sampling. Data collection equipment used in this study was a questionnaire. The Simple Linear Regression Method is used as an analytical method to determine the effect of the variables involved. The results of the analysis explain the role of job crafting on work engagement and job satisfaction in the company PT. Perta Arun Gas (PAG).